Trends in lung cancer mortality in Brazil from the 1980s into the early 21st century: age-period-cohort analysis Tendência de mortalidade por câncer de pulmão no Brasil de 1980 ao século 21: uma análise idade-período-coorte - Mirian Carvalho de Souza; Ana Glória Godoi Vasconcelos; Oswaldo Gonçalves Cruz (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2012)
The aim of this study was to describe the pattern of trends in lung cancer mortality in Brazil and identify the effects of the factors age, period and cohort (APC) on mortality rates. A time series study was conducted using secondary population-based data. Lung cancer mortality rates by sex were calculated for the period 1980 to 2007. APC models were adjusted to identify the influence of age, period and cohort effects on rates. Lung cancer mortality rates are significantly higher among men. Specific rates for men over the age of 64 and for women of all ages are increasing. There was a greater increase of adjusted rates among women. With respect to the age effect, mortality risk increases with age starting with the earliest age groups. With regard to the cohort effect, there is a lesser risk of mortality among men born after 1950 and an increasing risk across all cohorts among women. The results regarding younger generations indicate that present trends are likely to continue. The cohort effect among women suggests an increasing trend in mortality rates, whereas a decrease in rates among men under the age of 65 suggests that this trend will continue. These trends reflect tobacco control measures adopted since 1986. Os objetivos deste artigo foram descrever os padrões da tendência de mortalidade por câncer de pulmão no Brasil e identificar os efeitos dos fatores idade, período e coorte (APC) sobre as taxas. Foi realizado um estudo de série temporal utilizando dados secundários de base populacional. Taxas de mortalidade foram calculadas, por sexo, de 1980 a 2007. Modelos APC foram ajustados para identificar como idade, período e coorte influenciam as taxas. As taxas de mortalidade são mais elevadas entre os homens. As taxas específicas estão aumentando para homens maiores de 64 anos e mulheres de todas as idades. As taxas ajustadas cresceram mais entre as mulheres. O efeito idade revela um aumento do risco desde as idades mais precoces. O efeito coorte indica um menor risco para os homens nascidos desde 1950, e risco crescente para mulheres de todas as coortes. Os resultados para gerações jovens indicam que as tendências atuais devem continuar. O efeito coorte entre mulheres sugere um aumento do risco. Estas tendências refletem as medidas de controle do tabaco adotadas desde 1986.